Association between systemic Immune-inflammation index, systemic inflammation response index and adult osteoarthritis: national health and nutrition examination survey - Xiao-Jun Chen; Shu-Fen Liao; Qiu-Yi Ouyang; Ping Wang; Gui-Lan Huang; Shu-Yan Zeng; Qin Guo; Jin-Yan Li; Yang-Xi Shen; Na Li; Liu-Fang Huang; Feng-Qiu Gong (BMC Musculoskeletal Disorders)
Abstract Background Osteoarthritis (OA) is a degenerative and inflammatory joint disease caused by multiple factors, the underlying mechanisms of which are not fully understood. The systemic immune-inflammation index (SII) and systemic inflammation response index (SIRI) are both novel biomarkers and predictors of inflammation. Thus, this study aimed to evaluate the relationship between SII, SIRI and OA in adult. Objective The ultimate goal is to gain a deeper understanding of how SII, SIRI influences OA and the implications of this relationship. Materials and methods We analyzed data from 7204 participants aged 20 and older from the NHANES surveys conducted in 1999–2020, all of whom provided comprehensive data for this study. Standardized surveys assessed the presence of osteoarthritis and SII, SIRI. To thoroughly understand their relationship, we employed statistical techniques including multivariable logistic regression, stratified analysis with interaction, restricted cubic splines (RCS), and threshold effect analysis. Results A total of 7204 adult participants were enrolled, composing of 2830 (39.3%) male and 4374 (60.7%) female with a median age of 62.2 ± 13.9 years, 2955 (41.0%) were diagnosed with OA. Accordingly, A linear relationship between SII and OA was discovered after adjusting for underlying confounders, (p > 0.05) in RCS, and the association between the SIRI and OA exhibited a nonlinear relationship (p = 0. 042) in RCS. In the threshold analysis, the OR of developing OA was 1.648 (95% CI: 1.144 ~ 2.374, p < 0.05) in participants with SIRI of < 0.99 103 cells/ml. There was no significantly association between the SIRI and OA when the SIRI was ≥ 0.99 103 cells/ml. Further sensitivity analyses provided confidence that the results are robust and not likely to be substantially influenced by unmeasured confounding factors. Conclusions This cross-sectional study demonstrated that a linear relationship between SII and OA, and the association between the SIRI and OA was found to be nonlinear. Clinical trial number Not applicable.